2005
DOI: 10.1038/sj.eye.6702104
|View full text |Cite
|
Sign up to set email alerts
|

Emergency eye care in rural Australia: role of internet

Abstract: Purpose Significant differences exist in the utilization of emergency eye care services in rural and urban Australia. Meanwhile, influence of internet-based technology in emergency eye care service utilization has not been established. This study aims to demonstrate, from a health provider perspective, an internet-based service's impact on emergency eye care in rural Australia. Methods The teleophthalmology service was initiated in the Carnarvon Regional Hospital (CRH) of the Gascoyne region in Western Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 13 publications
0
33
0
1
Order By: Relevance
“…19,20 Pockets of electronic referral already exist within ophthalmology globally. 21,22 Furthermore, electronic referral has been shown to have lower startup costs than conventional services. 23 This may hold even greater benefit for developing countries and regions with geographically dispersed populations.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Pockets of electronic referral already exist within ophthalmology globally. 21,22 Furthermore, electronic referral has been shown to have lower startup costs than conventional services. 23 This may hold even greater benefit for developing countries and regions with geographically dispersed populations.…”
Section: Discussionmentioning
confidence: 99%
“…Community hospitals provide a wide range of services, across a broad spectrum of care provision, from preventative 38,39 and primary care 40,41 through to outpatient services, [42][43][44] inpatient medical care, 21,45 surgery, 46,47 minor injury care 48 and accident and emergency (A&E) care. 40,49 Within these broad areas, there was considerable diversity of the types of services provided, and a number of studies further reported on the implementation of new types and methods of service provision not previously available within the community hospital setting, such as point-of-care testing, 41 fracture clinics 50 or chemotherapy.…”
Section: Range Of Services Provided By Community Hospitalsmentioning
confidence: 99%
“…Models of teleophthalmology services exist between Carnarvon in North West Australia, where clinics are run by nurses and Perth consultant ophthalmologists (Figure 7). Patients detected to have an urgent sight threatening problem in Carnarvon are sent by helicopter for emergency treatment in Perth (Kumar S et al, 2006). Access to emergency treatment in rural areas can often mean the difference between life and death.…”
Section: Tele-ophthalmology In Australiamentioning
confidence: 99%
“…Access to emergency treatment in rural areas can often mean the difference between life and death. Internet-based technologies have the potential to provide earlier diagnosis and intervention, save lives and avoid unnecessary transfers from rural hospital emergency departments to urban hospitals (Kumar S et al, 2006) Benefits for rural healthcare staff in skills acquisition and education are also evident. There is a real need for ophthalmic emergency services in rural regional hospitals.…”
Section: Tele-ophthalmology In Australiamentioning
confidence: 99%